Applications and Mathematics Methods used in Software Engineering for Techniques Facial Recognition (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Facial recognition involves detecting a person and identifying their face. The tasks of searching and identification are not simple and depend heavily on the computational power of the platform used. Similar to the human eye's capability to detect and recognize a face within its range, computer systems require working with low-contrast images and applying various filters to minimize noise and interference. This process transforms images from low contrast to higher resolution, creating different feature vectors and matrices, and establishing various facial criteria for each stage of the system. The recognition of an individual through their face is precisely tuned by a comprehensive set of algorithms that operate based on mathematical theories and methods used in electronic systems to detect and identify human faces.